Hybrid unipolar-bipolar system with quasi-polarized code for free-space optical communication - Eddy Wijanto; Kevin Sutanto (Universitas Ahmad Dahlan, 2024)
In this study, the hybrid unipolar-bipolar (U-B) optical code division multiple access (OCDMA) with mixed unipolar-bipolar scheme in free-space optical communication was proposed. Additionally, the codeword assigned introduced the quasi-polarized code, which could be used to transmit both the unipolar and bipolar section. Using OptiSystem simulations, the model was studied. According to the results from the simulation, the proposed hybrid UB OCDMA can correctly decode the original optical signal from its matching encoder. Further testing of the hybrid U-B OCDMA system was conducted in turbulence conditions. According to the simulation results, walsh-zero cross correlation (ZCC) performs better than all other codes for the unipolar segment whereas walsh-hadamard (W-H) code performs best for the bipolar section. The simulations also showed that the performance deterioration of the walsh-ZCC algorithm was the greatest.